Komunikasi Humor dalam Film Si Paling Aktor: Analisis Semiotika Roland Barthes - Andre Aditriyanto; Didi Permadi; Ike Desi Florina (PERSPEKTIF, 2026)
Film functions not only as a medium of entertainment but also as a communication medium that represents various social messages through humor. Although studies on humor in Indonesian films have continued to develop, research specifically examining humor communication in Si Paling Aktor using Roland Barthes' semiotic approach remains limited. This study aims to analyze humor communication in Si Paling Aktor by interpreting the levels of denotation, connotation, and myth. The research employed a descriptive qualitative approach using Roland Barthes' semiotic analysis. Data were collected through observation of humorous scenes and analyzed based on denotative, connotative, and mythical meanings, supported by Arthur Asa Berger's humor theory. The findings reveal that humor communication in the film is constructed through six forms of humor: irony, satire, verbal humor, hyperbole, situational irony, and slapstick. At the denotative level, humor is expressed through dialogue, actions, facial expressions, and situations that generate comedic effects. At the connotative level, humor represents ambition, professionalism, the pursuit of social recognition, and everyday social dynamics, while at the mythical level it reproduces and critiques social constructions concerning social status, meritocracy, masculinity, validation culture, and standards of self-perfection. The findings demonstrate that humor in Si Paling Aktor functions not only as entertainment but also as an effective communication strategy for conveying social criticism, representing life values, and constructing cultural meanings.